2011
DOI: 10.2527/jas.2010-3658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of purified zearalenone on growth performance, organ size, serum metabolites, and oxidative stress in postweaning gilts1

Abstract: Zearalenone (ZEA), an estrogenic mycotoxin, is produced mainly by Fusarium fungi. Previous studies indicated that acute ZEA exposure induced oxidative stress and damage in multiple organs. Therefore, the present study was designed to investigate the adverse effects of dietary ZEA (1.1 to 3.2 mg/kg of diet) on oxidative stress and organ damage in postweaning gilts. A total of 20 gilts (Landrace × Yorkshire × Duroc) weaned at d 21 with an average BW of 10.36 ± 1.21 kg was used in the study. Gilts were housed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
94
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(112 citation statements)
references
References 41 publications
(45 reference statements)
16
94
2
Order By: Relevance
“…Therefore, these interleukins at pathological concentrations in the testis may injure the seminiferous epithelium, elevate the sensitivity and trigger some inflammation [49]. In accordance with the present findings, previous studies showed that exposure to ZEA also induced an intense inflammatory reaction as manifested [43][44][45]. These effects may help explain that the testicular immune structure could be disturbed by mycotoxins, such as ZEA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, these interleukins at pathological concentrations in the testis may injure the seminiferous epithelium, elevate the sensitivity and trigger some inflammation [49]. In accordance with the present findings, previous studies showed that exposure to ZEA also induced an intense inflammatory reaction as manifested [43][44][45]. These effects may help explain that the testicular immune structure could be disturbed by mycotoxins, such as ZEA.…”
Section: Discussionsupporting
confidence: 93%
“…The role of GST, as the phase II biotransformation enzyme in metabolic degradation of ZEA, has already been documented [8,9,14]. Supporting our findings, it was suggested that the depletion of antioxidants induced by ZEA could also be one of the reasons for increased oxidative stress in the testes and modifications of endocrine and reproductive parameters [17,45]. In contrast, our results revealed that lycopene treatment minimized the deleterious effects of ZEA on both testicular tissues and blood, such as the rise in testicular enzymes (GST, GPx and GR), testosterone and GSH levels and modulation of interleukins.…”
Section: Discussionsupporting
confidence: 82%
“…Increased relative liver weight in swine associated with DON feeding has also been reported by Bergsjø et al (1993). Although exposure to AFB1 and ZEA can increase relative liver weight (Jiang et al, 2011;Yarru et al, 2009), either individual or combination of AFB1 and ZEA did not affect the relative liver weight in our study. The similar divergences in body weight have also been shown when compared to other studies (Bergsjø et al, 1993;Jiang et al, 2011;Yarru et al, 2009).…”
Section: Discussionsupporting
confidence: 69%
“…Mycotoxins are reported to promote liver lesions, which can change liver enzymes and protein serum concentration in piglets (THIEU et al, 2008;JIANG et al, 2011). In our study, dietary exposure to ZEA, FB, and AF, at the tested levels, did not change the activity of the AST, GGT, or ALP enzymes (Table 2).…”
Section: Continuationmentioning
confidence: 47%
“…One typical signal in female piglets is the enlargement of the reproductive tract (JIANG et al, 2010b(JIANG et al, , 2011WANG et al, 2012). Alterations from the treatments on relative weights of reproductive tract (Table 2) was not detected.…”
Section: Ihc Of Tnf-α Marked Cells/fieldmentioning
confidence: 97%